Penerapan ISAK Nomor 35 atas penyajian laporan keuangan GMIM Betlehem Singkil Pancurang Kota Manado - Doaly, Zefanya Jeane; Alexander, Stanly W.; Rondonuwu, Sintje (Manajemen Bisnis dan Keuangan Korporat, 2025)
This study aims to analyze the implementation of the Interpretation of Financial Accounting Standards (ISAK) No. 35 in the preparation of financial statements at GMIM Betlehem Singkil Pancurang Church, Manado City. ISAK No. 35 provides guidelines for the financial reporting of non-profit entities to ensure greater accountability and transparency. The research employs a descriptive qualitative approach using interviews and documentation for data collection. The findings reveal that the church's financial statements have not yet fully adopted the ISAK No. 35 framework. The financial reporting is limited to a simple cash inflow and outflow report and does not include the five main components required by the standard, namely the statement of financial position, statement of changes in net assets, statement of activities, cash flow statement, and notes to financial statements. The application of ISAK No. 35 is therefore essential to enhance the church's financial accountability and transparency.